Dye sensitized solar cell-based optoelectronic device using novel [Ru(L1)(L2)(NCS)2] complex - Dayan, Osman; Imer, Arife Gencer; Tercan, Melek; Dere, Aysegul; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2021)
A dye sensitized solar cell-based photodiode was prepared using novel [Ru(L1)(L2)(NCS)(2)] complex for solar energy and optoelectronic applications. The new heteroleptic ruthenium(II) complex [Ru(L1)(L2)(NCS)(2)], was synthesized from the reaction of (pyridyl)benzimidazole ligands. The possible usage of [Ru(L1)(L2)(NCS)(2)] complex in dye synthesized solar cell-based photodiode was investigated using electrical and capacitance characteristics. The device was irradiated under various solar light intensities. The change in photocurrent of the device confirms the photoconducting behavior of prepared device. The device exhibited both the photocapacitance and photoresponse behavior with solar illumination. The obtained optoelectrical results suggest that the studied photodiode with [Ru(L1)(L2)(NCS)(2)] complex could be used in optoelectronic device for optical switching and controlling applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Ru complex; Photosensor; Photoresponse; Illumination effect